Current advancement of flexible dye sensitized solar cell: A review - Arith, Faiz; Noorasid, Nur Syamimi; Mohd Abid, Mohd Asyadi Azam; Muhammad Mustafa, Ahmad Nizamuddin; Mahalingam, Savisha; Chelvanathan, ‪Puvaneswaran; Amin, Nowshad (Elsevier GmbH, 2022)
In the last two decades, research on dye-sensitized solar cells (DSSCs) has shown tremendous improvement with promising findings. It has become one of the alternative options in replacing conventional silicon-based photovoltaics. Recently, a study towards the flexible form of solar cells has gained the attention of researchers. The features possess in DSSC such as high flexibility, light weight and environmentally friendly have made DSSC suitable for such purposes compared to rigid glass substrates. However, the biggest challenge faced by plastic-type substrates is temperature, where plastic substrates only withstand up to 150 ◦C before melting. In the DSSC fabrication process, temperatures as high as 400–500 ◦C are critically required for the purpose of material crystallization. With insufficient temperature during this process, poor interconnection between nanoparticles and increased electrode resistance will occur, thereby lowering the performance of plastic based DSSC. Here, we discuss the approaches that researchers have performed in solving the problem. Such approaches include the use of doctor blades, electrophoretic deposition, hydrothermal, peel and stick technique, and pulse laser deposition methods. In addition, this paper also discusses the most recent method which is additional procedure using Titanium (IV) tetraisopropoxide or UV-O3 treatment in the preparation of flexible DSSC. Several types of photoanode materials such as titanium dioxide, zinc oxide and graphene are also discussed in this paper.